New Leadership at UIN Syarif Hidayatullah Jakarta - Thaha, Idris (Studia Islamika, 2006)
In mid-October this year (17 October 2006), the University Senate at the Syarif Hidayatullah State Islamic University (UIN) Jakarta was convened with the task of electing a new rector for the University. The meeting, presided over by the outgoing rector Dr. Azyumardi Azra, was attended by eighty members of the University Senate. This number comprised of lecturers, assistant lecturers, and department head. Those in attendance included Dr. A. Malik Fajar (former Minister for Education), Dr. Din Syamsuddin (Head of Muhammadiyah), Professor M. Atho Mudzhar (Head of the Research and Development at the Department of Religion), Dr. Husni Rahim (Secretary of the National Higher Education Accreditation Board), and one of the leaders of MUI, Dr. Huzaemah Tahido. Amongst the more prominent of those absent - due to work commitments - were Dr. Quraish Shihab, Dr. Nasaruddin Umar, Dr. Said AqiI Husain al-Munawar, and Dr. Yunasril Ali.DOI: 10.15408/sdi.v13i3.565